Spinal dI4 Interneuron Differentiation From Human Pluripotent Stem Cells - Xu, Jia; Huang, Liang-Jiang; Fang, Zhengyu; Luo, Hong-Mei; Chen, Yun-Qiang; Li, Ya-Jie; Gong, Chen-Zi; Chen, Hong (Frontiers in Molecular Neuroscience, 2022)
Spinal interneurons (INs) form intricate local networks in the spinal cord and regulate not only the ascending and descending nerve transduction but also the central pattern generator function. They are therefore potential therapeutic targets in spinal cord injury and diseases. In this study, we devised a reproducible protocol to differentiate human pluripotent stem cells (hPSCs) to enriched spinal dI4 inhibitory GABAergic INs. The protocol is designed based on developmental principles and optimized by using small molecules to maximize its reproducibility. The protocol comprises induction of neuroepithelia, patterning of neuroepithelia to dorsal spinal progenitors, expansion of the progenitors in suspension and finally differentiation into mature neurons. In particular, we employed both morphogen activators and inhibitors to restrict or “squeeze” the progenitor fate during the stage of neural patterning, yielding highly enriched dI4 progenitors (90% Ptf1a+, 90.7% Ascl1+). The ability to generate enriched spinal dI4 GABAergic INs will likely facilitate the study of human spinal IN development and regenerative therapies for traumatic injuries and diseases of the spinal cord.